FAKTOR SOSIAL DAN BUDAYA DALAM PEMILIHAN PROGRAM STUDI ILMU PEMERINTAHAN: PERSPEKTIF MAHASISWA DI BERBAGAI DAERAH - supriadi, sudawan; Wahyuni, Sri (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
The selection of study programs is an academic decision that is influenced by social and cultural factors, in addition to interests and talents. This study aims to analyze the reasons why students choose the Bachelor of Government Studies Study Program at the University of Jambi and understand the influence of social and cultural factors in these decisions. The research uses a descriptive qualitative approach with primary data from in-depth interviews and observations, as well as secondary data from related documents. Data analysis was carried out using NVivo 12 Plus to identify key patterns and themes. The results of the study show that the selection of study programs is influenced by social factors such as the influence of family, friends, and the media, as well as cultural factors such as leadership values and community traditions. In addition, academic considerations and career prospects also play an important role. These findings highlight the importance of understanding social and cultural factors in designing recruitment strategies and academic guidance to increase student satisfaction and success.